Aging mechanisms of filled cross-linked polyethylene (XLPE) cable insulation material exposed to simultaneous thermal and gamma radiation. (August 2021) - Liu, Shuaishuai; Fifield, Leonard S.; Bowler, Nicola
Abstract: Thermal and simultaneous thermal and gamma radiation aging experiments were conducted on an industry grade cross-linked polyethylene (XLPE) cable insulation material, which is a composite material with XLPE as polymer matrix and various additives and fillers. Reverse engineering was conducted to identify and quantify the material composition given that this information was not revealed by the cable manufacture. Samples were then aged at temperatures of 60, 90, and 115 °C, exposed to gamma radiation for total doses of 0–324 kGy, and at dose rates of 0–540 Gy/h. Aging mechanisms were studied using various materials characterization techniques including pyrolysis gas chromatography mass spectrometry (Py-GCMS), differential scanning calorimetry (DSC), nuclear magnetic resonance spectroscopy (NMR), and gel-fraction tests. Results show that the flame-retardant components were decomposed into smaller molecules when the material was exposed to gamma radiation, while no changes were observed when the samples were aged thermally without gamma radiation. With exposure to gamma radiation, the crystalline phase of the XLPE were damaged by gamma radiation introducing defects in the crystals, resulting in smaller and less perfect crystals. The dominance of chain scission or chain reformation process largely depends on the chain mobility, which is decided by the aging temperature. Chain scission was seen to dominate when the material was exposed to gamma radiation at 60 °C. Chain cross-linking slightly dominated when the material was exposed to gamma radiation at 90 °C and became more dominant with exposure to gamma radiation at 115 °C. No significant change to the XLPE polymer matrix was observed when the samples were exposed to thermal aging without gamma radiation. Antioxidant is more effective in protecting the XLPE polymer matrix under thermal aging, but less effective with sample exposure to gamma radiation. Highlights: Flame retardants decompose into smaller molecules with gamma radiation. With gamma radiation, chain scission dominates at 60 °C. With gamma radiation, cross-linking slightly dominates at 90 °C and more at 115 °C. Antioxidant is effective protecting XLPE under heat, not as effective at gamma exposure. Gamma radiation causes defects in polymer crystalline phases.